Xenophobia as the major plight of African immigrants in South Africa: the example of Epiphanie Mukasano's selected poems - Abdullahi, Nafiu; Ali Termizi, Arbaayah; Kaur, Hardev; Muhammad Amin, Hasyimah (Routledge, 2024)
The attacks on African immigrants in South Africa have generated a lot of media attention both within and outside the country. This issue has not yet garnered enough critical attention in the field of literature, especially poetry. The purpose of this research is to analyse selected poems from Epiphanie Mukasano's collection Kilimanjaro on My Lap (2010) that discuss the hardships of African immigrants in South Africa. For the purposes of this study, this research uses migration theory. The research finds that racism and xenophobia are to blame for the country's immigration issues in the poems selected for the study. Asserting that the majority of immigrants are seeking protection due to upheaval in their home countries, Mukasano implores those who commit abhorrent acts of xenophobia and racism to have mercy on the immigrants. Consequently, Mukasano's answers to xenophobic assaults in the selected poems are addressed in this study. Mukasano makes an attempt to persuade the perpetrators of racism and xenophobia in South Africa that Pan-Africanism ought to be seen as a brotherhood rather than an enemy. Poems by Mukasano generally focus on the critical observation of people and their attitudes towards immigrants in general, regardless of their status, as well as the challenging consequences faced by black people. Protest poetry by Mukasano is vocal and engaged in challenging the status quo. Her tone, style, and use of poetic forms, which show how she gets her message across, show that she accomplished this successfully. © 2024 Informa UK Limited, trading as Taylor & Francis Group.